2018
DOI: 10.1016/s2468-2667(18)30068-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health care, hospital admissions, and mortality by ethnicity: population-based cohort study of health-system performance in Scotland

Abstract: SummaryBackgroundEthnic minorities often experience barriers to health care. We studied six established quality indicators of health-system performance across ethnic groups in Scotland.MethodsIn this population-based cohort study, we linked ethnicity from Scotland's Census 2001 (April 29, 2001) to hospital admissions and mortality records, with follow-up until April 30, 2013. Indicators of health-system performance included amenable deaths (ie, deaths avertable by effective treatment), preventable deaths (ie, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 40 publications
4
61
0
Order By: Relevance
“…As previous research (Bhopal et al 2012d;Gruer et al 2016;Bhopal et al 2018;Katikireddi et al 2018), we find that White Scottish experience poorer health compared to many minority populations, including White British, White Irish, White Polish and other White groups. Similarly to other previous work (Bhopal et al 2012a;Millard et al 2012;Bhopal et al 2015;Cezard et al 2016;Katikireddi et al 2018), we also find that the Pakistani population also has high rates of poor ill health, especially for ages 45 and above. Overall, while we have used self-rated health measures, our results are similar to the cited studies that have used objective measures of health, such as hospitalizations and mortality.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…As previous research (Bhopal et al 2012d;Gruer et al 2016;Bhopal et al 2018;Katikireddi et al 2018), we find that White Scottish experience poorer health compared to many minority populations, including White British, White Irish, White Polish and other White groups. Similarly to other previous work (Bhopal et al 2012a;Millard et al 2012;Bhopal et al 2015;Cezard et al 2016;Katikireddi et al 2018), we also find that the Pakistani population also has high rates of poor ill health, especially for ages 45 and above. Overall, while we have used self-rated health measures, our results are similar to the cited studies that have used objective measures of health, such as hospitalizations and mortality.…”
Section: Discussionsupporting
confidence: 82%
“…The research on health and ethnicity in Scotland has broadly come to either of two main conclusions: (1) the majority White Scottish population suffers poorer health than most other ethnicities, or (2) the South Asian population has a higher risk of ill health and mortality from specific diseases. Recent work has found that White Scottish men and women experience higher rates of cancer (Bhopal et al 2012d), higher mortality (Bhopal et al 2018), including preventable and amenable mortality (Katikireddi et al 2018), lower life expectancy (Gruer et al 2016), and worse selfrated health (The Scottish Government 2015) compared to most other larger ethnic groups. For example, both men and women of Asian and other White origin (except White Irish) can expect to live 2-6 years longer than White Scottish (Gruer et al 2016).…”
Section: Health and Ethnicity In Scotland And Elsewherementioning
confidence: 99%
See 2 more Smart Citations
“…a patient factor such as frailty) led to patients in that group experiencing negative implications for their patient safety thereby leading authors to conclude that the characteristic itself was a contributing/associated factor to the patient safety issue of interest. Four studies reported no discernible/neutral effect [36,59,84,92], two indicated a positive effect on patient safety [55,88] and one mixed effects as two outcomes were measured and had different directions [93]. This study defined culturally unsafe practice as any actions that diminish, demean, or disempower the cultural identity and well-being of an individual and applied this concept to health care.…”
Section: Description Of Contributory/associated Factorsmentioning
confidence: 99%